2016
DOI: 10.1007/s00405-016-4172-5
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of unknown primary tumor metastatic to neck nodes: role of elective irradiation

Abstract: In patients with squamous cell carcinoma (SCC) metastases to neck lymph nodes and unknown primary tumor, the role of elective irradiation of uninvolved neck and potential mucosal primary sites is yet to be determined. The aim of this study was to review the experience treating SCC of unknown primary metastatic to neck nodes with surgery and postoperative radiotherapy (PORT) in Slovenia between 1995 and 2010 and to determine the importance of the extent of irradiated volume. For this purpose, the nationwide Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“…This difference was anticipated to the fact that the mucosal region was contained in irradiated fields in the bilateral group. Strojan et al reported the comparison between involved-field and extended-field in postoperative setting (27). In multivariate analysis, the only factor that influenced locoregional control was the patients' age with older patients and the extent of RT field did not influence on any outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was anticipated to the fact that the mucosal region was contained in irradiated fields in the bilateral group. Strojan et al reported the comparison between involved-field and extended-field in postoperative setting (27). In multivariate analysis, the only factor that influenced locoregional control was the patients' age with older patients and the extent of RT field did not influence on any outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported similar results in HPV negative populations in recent years (114). Strojan et al found no significant difference when they compared the risk of metachronous second primary tumors in patients with known primaries, and the risk of appearance of a mucosal primary in NCUP patients who were diagnosed during the same time span and were postoperatively irradiated either with involved-field or extended-field technique (116). Certainly, with HPV-related cancer that has undergone tonsillectomies and partial lingual tonsillectomy, it appears even less likely for a primary to emerge in a delayed fashion (117).…”
Section: Treatmentmentioning
confidence: 77%
“…However, conflicting data were reported by authors who favored treatment of the ipsilateral neck only, stating that a thorough workup to discover the primary tumor was more worthwhile than prophylactic extensive irradiation because of the high morbidity such as xerostomia [28, 29]. As far as we known, the current prospective study was the largest study evaluating the treatment efficacy of retropharyngeal metastatic undifferentiated squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 95%